Impact of Social Structure Characteristics of High School and University Students Playing Fencing Sports on Collective Efficacy and Goal Orientation - Dilara Ilıkkan; Mehtap Yıldız (Selcuk University, 2022)
The aim of this study is to determine whether the social structural characteristics of high school and university students who participate in fencing are related to their collective efficacy and goal orientation. This study uses a descriptive (survey) research model based on quantitative observation. The research is limited to fencing athletes who are active in licensed, high school, and university education in 2020-2021 Academic Year. Task and Ego Orientation in Sport Questionnaire (TEOSQ), which was developed by Duda (8) to measure the goal orientation of fencing athletes participating in the study, was adapted for Turkish athletes by Toros (24), Collective Efficacy Scale (CES), which was developed by Riggs et al. (19) to measure their collective efficacies adapted for Turkish athletes by Öcel (18) and the socio-demographic information form were used to measure the characteristics of social structure. In the analysis, independent samples t-test, Pearson Correlation test, one-way analysis of variance test (Anova), Tukey post hoc test, and Tamhane's post hoc test were performed. As a result of the research, it was determined that there was no significant difference between the collective proficiency levels of the athletes according to gender, being a national athlete, educational status of their parents, duration of continuing fencing and family income. It was determined that there was a significant difference according to the number of cases. It has been determined that there is no significant difference between the goal orientation and sub-dimensions of the athletes according to gender, age, educational status, whether there are other licensed fencing athletes in the family, whether they are national athletes, duration of fencing, number of siblings and family income. While no significant relationship was found between collective efficacy and goal orientation and its sub-dimensions in male athletes and athletes over the age of 14, a significant relationship was found between collective efficacy and ego orientation in female athletes. While a significant relationship was found between goal orientation and its sub-dimensions, and between ego orientation and goal orientation in athletes aged 16 and older, no significant relationship was found between task and ego orientations in athletes aged 14-15.